Governance and Resource Policy Implications for Clinical Educator Doctors in Islamic Universities - Istiningsih; Hanif Faturrachim; Muhammad Lutfi Hamid; Ali Sodiq (University of Merdeka Malang, 2026)
Clinical doctors in teaching hospitals are increasingly required to perform dual roles as healthcare providers and medical educators. In State Islamic Higher Education Institutions (PTKIN), this duality is institutionally expected but administratively constrained by civil service regulations that enforce a single functional career pathway. This condition raises governance challenges related to career recognition, performance appraisal, and sustainability of clinical educator development. This study aims to examine the regulatory misalignment between the functional career pathways of clinical doctors and academic faculty and to analyze its implications for the governance of clinical educator career development within PTKIN. The study employed a qualitative normative–empirical design. Data were collected through a systematic review of regulations governing functional positions, teaching hospitals, and higher education governance, as well as document analysis of minutes from a Focus Group Discussion (FGD) between UIN Sunan Kalijaga and the National Civil Service Agency (BKN). Data were analyzed using content analysis, comparative policy analysis, and SWOT analysis to identify structural patterns and governance gaps. The findings reveal a structural misalignment between the dual role demands of doctors as clinicians and educators and the civil service principle of a single functional position. This misalignment results in limited recognition of academic contributions, uncertainty in career pathway transitions, and potential stagnation of academic career development for clinical educator doctors within PTKIN. This study highlights the need for integrative governance in managing hybrid academic–clinical careers and contributes to the literature on career governance by conceptualizing the tension between professional roles and bureaucratic regulation in public higher education institutions. It proposes an Integrative Governance Model emphasizing cross-sectoral regulatory harmonization, recognition of clinical educational activities, and alignment of performance appraisal systems to support sustainable career development in PTKIN. By conceptualizing clinical educator doctors as hybrid professionals, this study reframes career misalignment as a governance challenge and offers transferable insights for managing professional careers across clinical and academic domains in multi-sectoral public institutions